Deciphering the Mechanism of Siwu Decoction Inhibiting Liver Metastasis by Integrating Network Pharmacology and In Vivo Experimental Validation - Xuelei Chu PhD; Feiyu Xie PhD; Chengzhi Hou PhD; Xin Zhang MM; Sijia Wang MM; Hongting Xie MM; Chen An MM; Ying Li MM; Leyi Zhao MBBS; Peng Xue PhD; Shijie Zhu PhD (Integrative Cancer Therapies, 2024)
Background: Siwu Decoction (SWD) is a well-known classical TCM formula that has been shown to be effective as a basis for preventing and reducing liver metastases (LM). However, the active ingredients and potential molecular mechanisms remain unclear. Objective: This study aimed to systematically analyze the active ingredients and potential molecular mechanisms of SWD on LM and validate mechanisms involved. Materials and methods: The active ingredients in SWD were extracted by UHPLC-MS/MS in a latest study. Protox II was retrieved to obtain toxicological parameters to detect safety. Swiss Target Prediction database was exploited to harvest SWD targets. Five databases, Gene Cards, DisGeNET, Drugbank, OMIM, and TTD, were employed to filter pathogenic targets of LM. STRING database was utilized to construct the protein–protein interaction network for therapeutic targets, followed by Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis. GEPIA database and the Human Protein Atlas were taken to observe the expression of core genes and proteins. ImmuCellAI algorithm was applied to analyze the immune microenvironment and survival relevant to core genes. Molecular docking was performed to verify the affinity of SWD effective ingredients to core targets. In vivo experiments were carried out to validate the anti-LM efficacy of SWD and verify the pivotal mechanisms of action. Results: Eighteen main bioactive phytochemicals identified were all non-hepatotoxic. PPI network acquired 118 therapeutic targets, of which VEGFA, CASP3, STAT3, etc. were identified as core targets. KEGG analysis revealed that HIF-1 pathway and others were critical. After tandem targets and pathways, HIF-1/VEGF was regarded as the greatest potential pathway. VEGFA and HIF-1 were expressed differently in various stages of cancer and normal tissues. There was a negative regulation of immunoreactive cells by VEGFA, which was influential for prognosis. Molecular docking confirmed the tight binding to VEGFA. This study revealed the exact effect of SWD against LM, and identified significant inhibition the expression of HIF-1α, VEGF, and CD31 in the liver microenvironment. Conclusion: This study clarified the active ingredients of SWD, the therapeutic targets of LM and potential molecular mechanisms. SWD may protect against LM through suppressing HIF-1/VEGF pathway.